Paraoxonase-1 activity in type 2 diabetes mellitus with and without nephropathy - Nehal H El-said; Mohammed M Nasr-Allah; Noha A Sadik; Saher A Sharaf (SpringerOpen, 2015)
Background Paraoxonase-1 (PON-1) is an enzyme synthesized in the liver that has antioxidant functions as it binds to the HDL particles and prevents the oxidation of LDL, which possibly plays a role in the prevention of atherosclerosis and coronary artery disease. Objectives To determine PON-1 activity in type 2 diabetic patients with and without diabetic nephropathy and its correlation with the lipid profile, disease duration, and glycemic status. Patients and methods This study was carried out on 30 patients with type 2 diabetes mellitus who attended the diabetes and endocrine clinic at Kasr Al Ainy Hospital, Cairo University, including 20 patients with evidence of diabetic nephropathy and 10 patients without diabetic nephropathy as well as 15 healthy age-matched control participants. Fasting blood sugar, 2 h postprandial blood sugar, total cholesterol, HDL, LDL, triglycerides, and serum creatinine were measured. PON-1 activity was detected using a colorimetric method. Results PON-1 activity was reduced significantly in diabetic patients with and without nephropathy, with mean 226.1 ΁ 135.4 and 221.7 ΁ 119.6 nmol/ml/min, respectively, versus 758.5 ΁ 353.9 nmol/ml/min in the control group (P < 0.001). PON-1 activity was not significantly different between diabetic patients with and without nephropathy. PON-1 activity was correlated negatively with HDL (r = −0.496, P = 0.026) in diabetic patients with nephropathy. PON-1 activity was not correlated significantly with disease duration and glycemic status. Conclusion PON-1 activity was significantly reduced in type 2 diabetes, but did not differ between diabetics with or without nephropathy.